The Influence of Digital Business Education and Perceived Usefulness on The Use of The Shopee Marketplace On The Digital Entrepreneurship Intention of University Students - Nadila, Salsaufy Brillian; Pratikto, Heri; Hermawan , Agus (Journal of Applied Business, Taxation and Economics Research, 2024)
This study aims to examine the effect of Digital business on Digital entrepreneurship intention and perceived usefulness on Digital entrepreneurship intention. The type of research used in this research is quantitative research. The type of data in this study uses primary data. The analysis method used is multiple linear regression analysis using the SPSS 23 program. The population taken by researchers is undergraduate students of the Faculty of Economics and Business. The sampling technique in this study was purposive sampling, namely with predetermined criteria. Based on the purposive sampling method, 369 respondents were obtained who met the criteria. The results of hypothesis testing in this study indicate that digital business education has a positive and significant effect on digital entrepreneurship intention. Perceived usefulness has no direct effect on digital entrepreneurship intention. Shopee marketplace customers have a direct effect on Digital Entrepreneurship Intention. Digital business education has a direct effect on the Shopee marketplace. Perceived usefulness has a direct effect on the Shopee marketplace. There is a simultaneous influence of digital business education through the Shopee marketplace on digital entrepreneurship intention. There is a simultaneous influence of perceived usefulness through the Shopee marketplace on digital entrepreneurship intention